Impact of Administrative Empowerment on Organizational Commitment: A Case Study of Taj Sheba Hotel in Yemen - Abdulrahman Mohammed Al- Sufyani; Adel Qaid F. Al- Ameri (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2021)
The aim of this study is to analyze the impact of administrative empowerment on the organizational commitment among the employees of Taj Sheba Hotel in the Republic of Yemen. The research is based on the descriptive approach using questionnaire which consists of 40 questions with 5 Likert scale. The data was distributed and collected from 100 employees working at Taj Sheba Hotel. The results indicate that the levels of administrative empowerment and organizational commitment of the employees at Taj Sheba Hotel are high. Also, the results show that there is a statistically significant impact of administrative empowerment dimensions (simultaneously) on organizational commitment of employees. Besides, all dimensions of administrative empowerment (job autonomy – motivation – communication – teamwork – training) used in this study have a significant impact on organizational commitment. Further, the results show that an estimated 64.2% of the variance in overall organizational commitment can be accounted for by the five dimensions of administrative empowerment, in which job autonomy was the most important factor in increasing the organizational commitment (β = 0.350) followed by training in the second rank (β = 0.242), then communication in the third rank (β = 0.211), motivation in fourth rank    (β = 0.193) and teamwork in the last rank (β = 0.190). Finally, suggestions may be made to Taj Sheba Hotel administration to pay more attention to administrative empowerment as a new strategy and an effective route for development, improvement of quality and enhancement of organizational commitment.